Note—When Does Lag Structure Really Matter … Indeed? - Bultez, Alain; Naert, Philippe (Management Science, 1988)
Magat et al. (Magat, W. A., J. M. McCann, R. C. Morey. 1986. When does lag structure really matter in optimizing advertising expenditures? Management Sci. 32(February) 182–193.) have correctly pointed out that a high sales elasticity to advertising adds to the flatness of the advertiser's profit objective. Quite consistently, apparently, they deduce that when the goodwill elasticity is huge, as with the famous Lydia Pinkham's vegetable compound, the misidentification of the distribution of advertising dynamic effects should hardly hit the advertiser's performance. But building on their approach, we show here it is just in such cases that the misspecification of the lag pattern is likely to cause the most severe damages. As those losses appear small, we persist in believing that econometric sophistication of lag structures may not pay much.